Genome Sequencing and Analysis of the Hypocrellin-Producing Fungus Shiraia bambusicola S4201 - Zhao, Ning; Li, Dan; Guo, Bing-Jing; Tao, Xin; Lin, Xi; Yan, Shu-Zhen; Chen, Shuang-Lin (Frontiers in Microbiology, 2020)
Shiraia bambusicola has long been used as a traditional Chinese medicine and its major medicinal active metabolite is hypocrellin, which exhibits outstanding antiviral and antitumor properties. Here we report the 32 Mb draft genome sequence of S. bambusicola S4201, encoding 11,332 predicted genes. The genome of S. bambusicola is enriched in carbohydrate-active enzymes (CAZy) and pathogenesis-related genes. The phylogenetic tree of S. bambusicola S4201 and nine other sequenced species was constructed and its taxonomic status was supported (Pleosporales, Dothideomycetes). The genome contains a rich set of secondary metabolite biosynthetic gene clusters, suggesting that strain S4201 has a remarkable capacity to produce secondary metabolites. Overexpression of the zinc finger transcription factor zftf, which is involved in hypocrellin A (HA) biosynthesis, increases HA production when compared with wild type. In addition, a new putative HA biosynthetic pathway is proposed. These results provide a framework to study the mechanisms of infection in bamboo and to understand the phylogenetic relationships of S. bambusicola S4201. At the same time, knowledge of the genome sequence may potentially solve the puzzle of HA biosynthesis and lead to the discovery of novel genes and secondary metabolites of importance in medicine and agriculture.